REBUSAN DAUN SIRSAK EFEKTIF MENURUNKAN KADAR ASAM URAT PADA PENDERITA GOUT ARTRITIS DI KELURAHAN LAWANGAN DAYA KABUPATEN PAMEKASAN - Putri, Lusi Erlina; Utami, Nurul (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Excessive uric acid will not be completely accommodated and metabolized by the body, so there will be an increase in uric acid levels in the blood which is known as peruricemia. Gout disorders are characterized by a sudden attack in the joint area. The pain that occurs generally appears suddenly. This sudden appearance often makes it difficult for gout sufferers to move. The aim of this study was to test the effectiveness of giving boiled soursop leaves to reduce uric acid levels in elderly women suffering from gouty arthritis. The sample for this research was 14 elderly women suffering from gouty arthritis in Lawangan Daya District. Data were collected using an observation sheet, the results of testing uric acid levels were analyzed using the Paired T Test statistical test using SPSS. The results of the study showed P<0.05, meaning there was a significant reduction in the administration of boiled soursop leaves on the uric acid levels of elderly women suffering from gouty arthritis in Lawangan Daya Village, Pamekasan Regency. Seeing the results of this research, it is necessary to give decoction of soursop leaves regularly.The conclusion of this research is that giving decoction of soursop leaves has been proven to be effective in reducing uric acid levels in sufferers of Gouty Arthritis. Soursop leaf decoction can be used as a herbal medicine that has no side effects for sufferers or respondents.Keywords : Soursop Leaves, Gouty Arthritis, Elderly Women